Harmony of National Idea and Values in Forming Complete Young People in the Period of Global Changes - Tulkin, Kuyliyev; Nadira, Rakhmonberdiyeva (Miasto Przyszłości, 2024)
The article is devoted to the development of national ideology and democracy, in particular, national identity, the need to study the ancient and rich history of our Motherland and the harmony of ethnic, national and universal values. It is a fact that the sharp struggle in the information field of the 21st century is recognized as one of the harsh realities of the new century, which is becoming a tradition. At such a time, one of the urgent tasks should be the rallying of the nation towards a great future and ambitious goals, the education of a high-quality, mature generation, the education of people who are mature in all respects. After all, the role of education in the development of intellectual knowledge and intellectual potential in the formation of comprehensively developed youth is incomparable. The article reveals that spiritual education is a decisive factor in the upbringing of mature youth.